GENDER INEQUALITY BEFORE THE LAWS AS SEEN IN ON THE BASIS OF SEX FILM BY MIMI LEDER - Fuji Lestari (Nazharat: Jurnal Kebudayaan, 2021)
In this study, researcher analyzes an inequality film written by Daniel Stiepleman and directed by Mimi Leder. This Film tells the strory about inequality dan women struggle. Therefore the researcher entitled this research with “Gender Inequality before the Laws as seen in On the Basis Of Sex film by Mimi Leder”, This study aimed to discuss; 1) injustice between a man and a woman before the law, 2) how women try to resist the laws. Design of this research was qualitative descriptive research. The researcher applied the theory of human rights and feminist legal theory by Universal Decralation of human right and Judith and remer to answer the research question problem formulation. Sociological approach also used in this research. In collecting the data, the researcher used technique of documentation. The technique used in analyzing data in this study was a descriptive technique. The results of this research are; 1) there are four gender inequalities depicted in the film on the basis of sex; (a) inequality in economic right (b) inequality in education right (c) inequality in social right (d) inequality in civil right 2) women's efforts to fight the law are three ways (a) Speak Out the Own Experiences (b) support other campaigners (c) exspressing rational opinions.